Isolation, identification and pathogenicity of fungal organisms causing postharvest rot of sweet oranges, cucumber and lettuce in Sharada Market, Kano State-Nigeria - Mukhtar, Ya’u; Muhammad, Maryam Adamu; Zubairu, Safiyya Maiwada; Galalain, Aisha Muhammad; Ahmad, Umar Muazu (Asian Journal of Medical and Biological Research, 2020)
Isolation, identification and pathogenicity of fungal organisms responsible for the postharvest spoilage of sweet oranges, cucumber and lettuce at Sharada market in Kano metropolis, Nigeria was carried out in the present study. Samples showing symptoms of rot were collected from the retailers in the market and conveyed to the laboratory using polyethene bags. Small portion from rotten parts were cut and surface sterilized in 1% of Sodium hydrochloride and rinsed in several changes of sterile distilled water. They were plated on Potato Dextrose Agar (PDA) and observed for fungal growth. Identification was done macroscopically and microscopically. For pathogenicity test, healthy sweet oranges, cucumber and lettuce were plugged with pure cultures of the fungal isolates, thus, frequency of occurrence and disease severity of the pathogen were evaluated. Seven fungi namely Rhizopus spp., Aspergillus flavus, Mucor spp., Aspergillus fumigatus, Aspergillus niger, Fusarium oxysporum, Rhizoctonia spp. and Fusarium oxysporum were isolated. Severity of decay ranged from 6.39–46.15% for all fungal isolates, while the controls showed 0%. Pathogenic microorganisms on fruits and vegetables are a potential health hazard to man and animals following ingestion. Proper handling from the farm as well as during storage and the avoidance of mixing of diseased ones with the healthy ones were identified as important factors in preventing loss and health complication at the event of consumption. The use of suitable chemical treatment of the orange is also recommended as means of reducing economic loss due to fungal pathogens. Asian J. Med. Biol. Res. June 2019, 5(4): 286-291